RUANG LINGKUP MANAJEMEN PENDIDIKAN: KAJIAN LITERATUR TERHADAP TUGAS DAN TANGGUNG JAWAB PENGELOLA SEKOLAH - Salsalia Firdausia; Muhamad Taufik; Muhammad Hasan Basari (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This article discusses the scope of educational management through a literature review that focuses on the duties and responsibilities of school administrators. Educational management is a vital process in ensuring the effectiveness and efficiency of educational institutions. It includes a series of activities such as planning, organizing, directing, and supervising all educational resources to achieve learning objectives. This study uses a qualitative approach with a systematic literature review. Data were collected from academic journals, books, and government regulations published between 2015 and 2024. The results show that the scope of educational management includes several core areas such as curriculum management, student affairs, human resource management, facilities and infrastructure, finance, and school-community relations. The duties and responsibilities of school administrators are not only administrative but also leadership-oriented, innovative, and accountable to stakeholders. The study concludes that effective school management requires competence, collaboration, and continuous professional development for educational leaders.